GPS Devices as a Part of Geographical Education in School–A (Non)Useful Way of Learning in Context of Spatial Orientation? Ergebnisse einer empirischen Studie zu den Kompetenzerwerbschancen im Geographieunterricht der Jahrgangsstufen 5, 6 und 8 - Neeb, Kerstin (Journal of Geography Education, 2013)
Spatial orientation using GPS-devices constitutes a modern geographical method of practice which should be part of geographical education in school. Questions concerning the way of teaching, the adequate age of pupils and eventually problems in the process of learning have not been explored empirically in the academic community so far. This survey aims to give answers to these questions as well as to determine first trends of possibilities of competence-based learning. Additionally this pilot study will show up future aspects for further research in the context of GPS-based spatial orientation.